Fabrication of bacterial nanocellulose/polyethyleneimine (PEI-BC) based cationic adsorbent for efficient removal of anionic dyes - Thorat, Meghana N.; Jagtap, Ashish; Dastager, Syed G. (Journal of Polymer Research, 2021)
A bacterial cellulose (BC) based adsorbent was prepared by using polyethyleneimine (PEI) using epichlorohydrin as a cross-linker. The physicochemical characterization of the of the developed adsorbent was carried out using FTIR, BET analysis and SEM, respectively. The dye removal efficiency of the adsorbent was assessed towards two anionic model dyes viz. congo red (CR) and reactive red 120(RR). The kinetic data for the removal of both the anionic dyes were fitted better using pseudo-second-order model. Langmuir model describes well the process of adsorption with predicted maximum adsorption capacity (q(max)) 515.46 and 300.3 mg L-1 for CR (at pH 6.0) and RR (at pH 3.0) respectively. The adsorption-desorption study showed that PEI-BC adsorbent is effective with more than 90% dye removal efficiency even after four cycles. Furthermore, the bactericidal activity of the adsorbent was analysed using Escherichia coli and Staphylococcus aureus and adsorbent showed good inhibition against both test organisms. The study reveals that PEI-BC adsorbent can be a good candidate for water remediation purpose bearing multifunctional behaviour.
Keywords: adsorbent; Anionic dyes; Bacterial cellulose; Bactericidal; Polyethyleneimine

Bacterial nanocellulose: a versatile biopolymer production using a cost-effective wooden disc based rotary reactor - Jagtap, Ashish; Dastager, Syed G. (Biopolymers, 2024)
Bacterial nanocellulose (BNC) has various unique qualities, including high mechanical strength, crystallinity, and high water-holding capacity, which makes it appropriate for a wide range of industrial applications. But its lower yield coupled with its high production cost creates a barrier to its usage. In this study, we have demonstrated the better yield of BNC from an indigenous strain Komagataeibacter rhaeticus MCC-0157 using a rotary disc bioreactor (RDB) having a wooden disc. The RDB was optimized based on the type of disc material, distance between the disc, and rotation speed to get the highest yield of 13.0 g/L dry material using Hestrin-Schramm (H-S) medium. Further, the bioreactor was compared for the BNC production using reported medium, which is used for static condition; the RDB showed up to fivefold increase in comparison with the static condition reported. Komagataeibacter rhaeticus MCC-0157 was previously reported to be one of the highest BNC producing stains, with 8.37 g/L of dry yield in static condition in 15 days incubation. The designed RDB demonstrated 13.0 g/L dry yield of BNC in just 5 days. Other characteristics of BNC remain same as compared with static BNC production, although the difference in the crystallinity index was observed in RDB (84.44%) in comparison with static (89.74%). For the first time, wooden disc was used for rotary bioreactor approach, which demonstrated higher yield of BNC in lesser time and can be further used for sustainable production of BNC at the industrial level. image
Keywords: bacterial nanocellulose; rotary reactor; Sustainability; wooden disc

Bacterial nanocellulose (BNC) produced from sorbitol as a sustainable nano-filter for oil-water separation - Jagtap, Ashish; Krushnatray, Ajinkya; Dastager, Syed G. (International Journal of Biological Macromolecules, 2025)
Oil spillage is one of the serious problems for sustainable environment. Bacterial nanocellulose (BNC), a hydrophilic and highly porous material holds a promising material for oil-water separation from contaminants. In the present work, a hydrophilic BNC produced from a sorbitol as the carbon source demonstrated the unique porous symmetrical arrangement having an oleophilic property. The BNC membrane obtained showed the highest water holding capacity (WHC) of approximate to 147 gg 1 . The Brunauer-Emmett-Teller (BET) analysis of BNC revealed the unique characteristics of isothermic patterns, having macro sized pores with diameter of 121.3 nm and surface area of 40.6m2/g, which plays a vital role in separation of oil from water by allowing passage of only water through it. The separation efficiency of BNC membrane produced after 5th day of incubation has showed 99.0 % oil removal compared to 10 and 15th day incubated BNC membranes. a CFD model to investigate the possibilities of BNC membranes and clarify the dynamics of oil-water separation. The nanostructured network of BNC offers a tortuous path for oil molecules while allowing rapid permeation of water, leading to high separation selectivity and flux. Although BNC has been previously studied for oil water separation, this study provides new insights into the use of wet BNC membranes into its pristine state with sorbitol as carbon source for this application.
Keywords: bacterial nanocellulose; Macro porous; Oil-water separation; Sorbitol

Bacterial nanocellulose enhances osteogenic activity of Vat-based 3D-bio-printed silk fibroin hydrogels - Waidi, Yusuf Olatunji; Jagtap, Ashish; Dastagar, Syed G.; Chatterjee, Kaushik (International Journal of Biological Macromolecules, 2025)
Tissue engineering, particularly leveraging three-dimensional (3D) bioprinting, is emerging as a transformative solution to repair critical-size bone defects. However, identifying suitable biomaterials remains a key technological bottleneck in the field. Toward this broader goal, this study explored a composite bioink containing photocurable silk fibroin (SF) and bacterial nanocellulose (BNC) for fabricating scaffolds for bone tissue engineering (BTE) by 3D bioprinting using digital light projection (DLP). We prepared scaffolds with 0, 0.25, and 0.75 wt% BNC and characterized their physicochemical properties (degradation, viscoelasticity, porosity, compressive strength). We assessed samples in simulated body fluid (SBF) after 14 days to evaluate biomineralization. Additionally, using MC3T3-E1 preosteoblast cells, we examined cell viability, metabolic activity, proliferation, and osteogenic potential through alkaline phosphatase (ALP), Alizarin Red S (ARS), von Kossa, hematoxylin and eosin (H&E), and Picrosirius Red assays. The optimized bioinks produced hydrogels with controlled degradation, tunable viscoelasticity, interconnected pores, and significantly improved compressive strength. Specifically, 10 % methacrylated-silk with 0.75 % BNC (Silk-MA/0.75BNC) showed superior mechanical properties compared to 10 % Silk-MA or 10 % Silk-MA with 0.25 % BNC (Silk-MA/0.25BNC). In vitro studies confirmed enhanced biomineralization with Silk-MA/0.75BNC, increased calcium deposits, and improved cell viability and metabolic activity with BNC incorporation. Hence, the 3D-bioprinted composite scaffolds were shown to effectively support cell proliferation, with the 0.75 % BNC bioink significantly stimulating osteogenic markers. These results underscore the potential of Silk-MA/BNC composite bioinks for advanced 3D bioprinting of BTE constructs.
Keywords: Additive manufacturing; bacterial nanocellulose; Bone repair; Methacrylated silk fibroin